1993
DOI: 10.1093/carcin/14.10.2119
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations in phenacetin-associated human urothelial carcinomas

Abstract: Chronic abuse of the analgesic drug phenacetin is associated with an increased risk of development of transitional cell carcinomas of the urinary tract. It is unclear whether phenacetin acts through chronic tissue damage (phenacetin nephropathy) or via a genotoxic metabolite causing promutagenk DNA lesions. In the present study, we investigated 15 urothelial carcinomas from 13 patients with evidence of phenacetin abuse. Tumors were screened for p53 mutations in exons 5-8 by single-strand conformation polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…This was suggested to reflect a response to air pollution toxicity. TP53 mutations in PA-associated urothelial carcinomas (Petersen et al, 1993) have been reported, but show variability. Microsatellite instability was found in about 40% of RE sinonasal carcinomas (Uryu et al, 2005).…”
Section: Human Effects Of Rodent Nasal Carcinogensmentioning
confidence: 99%
“…This was suggested to reflect a response to air pollution toxicity. TP53 mutations in PA-associated urothelial carcinomas (Petersen et al, 1993) have been reported, but show variability. Microsatellite instability was found in about 40% of RE sinonasal carcinomas (Uryu et al, 2005).…”
Section: Human Effects Of Rodent Nasal Carcinogensmentioning
confidence: 99%
“…In a previous study, 3 of the 8 p53 mutations detected in phenacetin-associated urothelial carcinomas were G:C=A:T transitions at CpG sites (Petersen et al, 1993). This mutation type is considered to result from spontaneous deamination of 5-methylcytosine and is more likely to be a consequence of chronic tissue damage than of promutagenic DNA lesions by metabolites of phenacetin.…”
mentioning
confidence: 95%
“…However, most of the molecular genetic studies (eg, Goto et al, 1997;Habuchi et al, 1993;Petersen et al, 1993;Spruck et al, 1994;Xu et al, 1996) have focused mainly on invasive and high-grade cancers. The determination of identical genetic alterations in later stages of tumor development could reflect monoclonal occurrence of multiple tumors as well as dominant overgrowth of the most malignant tumor cell clone, the latter mimicking monoclonality.…”
mentioning
confidence: 99%